Alleviating Pregastroscopy Anxiety Using Mobile Social Media Application - Lu, Dan; Wang, Jing-Hua; Lu, Chao; Liu, Zheng-Lv; Jain, Ajay; Ji, Feng; Gu, Qing (Frontiers in Medicine, 2022)
Aim The research aimed to study the effect of using WeChat (a mobile social media application) on pregastroscopy anxiety and the cooperation of patients with different coping styles. Methods In order to decrease patients’ pregastroscopy anxiety and improve the tolerance of unsedated gastroscopy, WeChat, a widely used mobile social media application, was applied to provide information prior to their endoscopic procedure. Two hundred and thirty (230) patients who underwent initial unsedated gastroscopy in a large teaching hospital in China were classified into two groups based on their coping style: information seekers or information avoiders, using the Information Subscale of the Krantz Health Opinion Survey (KHOS-I). Each of the two groups was prospectively randomly assigned to either receiving the brochure information or conjunctive interactive WeChat-delivered information of gastroscopy. State anxiety assessed by the State Anxiety Scale of Spielberg’s State-Trait Anxiety Inventory, blood pressure, and heart rate were measured at enrollment, upon arrival, and before gastroscopy. Results Information seekers and avoiders who received information from the brochure and the WeChat platform experienced significantly less state anxiety upon arrival and before gastroscopy. Furthermore, information seekers who received information from the conjunctive WeChat platform had lower frequency of retching, lower scores of nausea and bloating, and better tolerance. Information avoiders who received information from the conjunctive WeChat platform had lower frequency of retching, lower scores of discomfort while swallowing the scope and nausea, and better tolerance. However, we found information delivered via WeChat is less preferred than information delivered by brochure at the initial questionnaire. No significant difference was found in blood pressure or heart rate upon arrival and before gastroscopy. Conclusions Although people prefer to receive information via brochure, the provision of gastroscopy information through a mobile social media application, such as WeChat, could significantly reduce patients’ pregastroscopy anxiety, lower the frequency of retching, the scores of nausea and bloating, and improve tolerance for information seekers. In addition, it could lower the frequency of retching, the scores of discomfort while swallowing the scope, and its concurrent nausea and improve tolerance for information avoiders.